2010
DOI: 10.2139/ssrn.1677348
|View full text |Cite
|
Sign up to set email alerts
|

Firm’s Information Environment and Stock Liquidity: Evidence from Tunisian Context

Abstract: This paper analyzes the relationship between public disclosure, private information and stock liquidity in the Tunisian market. We use a sample of 41 listed firms in the Tunis Stock Exchange in 2007. First, we find no evidence that there is a relation between public and private information. Second, Tunisian investors do not trust the information disclosed in both annual reports and web sites, consequently it has no effects on stock liquidity, in contrast with private information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…This may reduce the importance of earnings in assessing corporate risk credit, as banks have the ability to reduce the costs of adverse selection for borrowers. Loukil and Yousfi (2012) and more recently Houcine (2017) reported that in a code-law country, namely Tunisia, investors do not trust public financial information and rely more on private information to reduce information asymmetry. Similarly, Talbi and Omri (2014) show that voluntary disclosure reduces the cost of debt for Tunisian listed companies.…”
Section: Earnings Quality and Cost Of Debt: Literature Review And Hypmentioning
confidence: 99%
“…This may reduce the importance of earnings in assessing corporate risk credit, as banks have the ability to reduce the costs of adverse selection for borrowers. Loukil and Yousfi (2012) and more recently Houcine (2017) reported that in a code-law country, namely Tunisia, investors do not trust public financial information and rely more on private information to reduce information asymmetry. Similarly, Talbi and Omri (2014) show that voluntary disclosure reduces the cost of debt for Tunisian listed companies.…”
Section: Earnings Quality and Cost Of Debt: Literature Review And Hypmentioning
confidence: 99%